A low-noise tire tread rubber and preparation method thereof
By using the combination of boron nitride composite fillers and modified porous ceramic particles in tire tire glue, the problem of being easy to peel off and tire glue performance in existing technologies is difficult to take into account. Tire tire gums with strong sex and superiority.
Patent Information
- Application Number
- CN202411524628.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-30
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2044-10-30
AI Technical Summary
When the prior art reduces tire noise, the embedded sound-absorbing material is easily peeled off, which cannot guarantee the durability of noise reduction. At the same time, while reducing noise, the tensile strength and hardness of the tread glue are difficult to maintain.
The combination of boron -nitride composite filler and modified porous ceramic particles is used to prepare low -noise wheel tire tire tire gum. Boron -nitride composite fillers absorb and block sound waves through the hollow structure of microspheres, and modified porous ceramic particles consume sound wave energy energy through porous channel structures, combined with use to enhance the noise reduction and sound insulation effect.
Significantly reduce tire noise, maintain the durability of noise reduction, and at the same time improve the stretch strength and hardness of tire glue, and improve the stability and safety of tires.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polymer compound compositions, and in particular relates to a low-noise tire tread rubber and a preparation method thereof. Background Art
[0002] When the vehicle speed exceeds 60km / h, tire noise becomes the main component of vehicle driving noise. The deformation and vibration of the tire when rolling and the vibration and friction generated when the tire contacts the ground constitute the main noise source of tire noise. This noise that easily makes people feel irritated and tired not only affects the comfort of drivers and passengers, but also may cause interference to the surrounding environment and residents.
[0003] In the prior art, in order to reduce tire noise, the tire pattern, structure, tread rubber material, etc. are generally designed specifically, or suitable sound-absorbing materials are embedded in the tire to reduce the impact of noise.
[0004] CN112659819A discloses a structure for reducing tire cavity noise, which can reduce cavity noise by pasting a sound-absorbing cotton layer and a sound-absorbing cloth layer inside the tire and combining the disturbance of the air in the tire cavity by a lightweight sphere; CN110039964A discloses a low-noise pneumatic tire, in which a noise absorber is installed in the tire cavity, and the noise absorber is set to have a variable acoustic impedance in the circumferential direction of the tire, thereby reducing the overall noise energy of the cavity resonance. The above patents all embed sound-absorbing materials into the tire to reduce the impact of noise, but the embedded sound-absorbing materials are easy to peel off after the tire has been running for a long time, and the durability of noise reduction cannot be guaranteed.
[0005] CN113929960A discloses a lower tread rubber composition and a pneumatic tire for reducing tire noise. The tire noise can be significantly reduced by foaming the lower tread of the tire to produce a microporous structure. However, in the actual production process, rubber foaming may encounter some problems, such as insufficient foaming holes, uneven foaming holes, over-vulcanization or under-vulcanization, etc., which make the production process difficult to control. In addition, the strength and hardness of the rubber are significantly reduced after micro-foaming, which affects the handling stability of the tire using the rubber.
[0006] CN116656021A discloses a tread rubber with noise reduction performance, a preparation method thereof and a tire. The invention adopts a noise reduction mixture made of a modified polymer and a compound hollow microsphere, which absorbs the energy in the vibration noise and blocks the transmission of part of the sound waves to play a role in silencing. However, the noise reduction effect of the modified polymer in the noise reduction mixture is weak, and the main noise reduction effect is played by the hollow glass microspheres, but the hardness of the hollow glass microspheres is low. After being added to the rubber, it will not only reduce the mechanical properties of the rubber product, such as tensile strength, but also because it is relatively fragile, it is easy to break during the tread rubber preparation process and the tire running process, affecting the noise reduction effect of the tire made of the tread rubber. Summary of the invention
[0007] In view of the deficiencies in the prior art, the present invention provides a low-noise tire tread rubber and a preparation method thereof, which can significantly reduce tire noise and maintain the durability of the noise reduction. While reducing tire noise, the tensile strength and hardness of the tread rubber are guaranteed, thereby improving the handling stability of the tire using the tread rubber.
[0008] In order to solve the above technical problems, the technical solution adopted by the present invention is as follows:
[0009] A method for preparing a low-noise tire tread rubber comprises the following steps: preparing a boron nitride composite filler, preparing modified porous ceramic particles, and refining the rubber;
[0010] The preparation of the boron nitride composite filler includes preparing boron nitride hollow microspheres and modifying the boron nitride hollow microspheres;
[0011] The method for preparing hollow boron nitride microspheres comprises: preparing water, 2-methyl-1,3-butadiene, hexagonal boron nitride and polyvinyl pyrrolidone into a mixed solution, controlling the temperature of the mixed solution to be 10-12° C., stirring and dispersing the mixed solution uniformly, ultrasonically treating the mixed solution for 2-3 minutes, stirring the mixed solution at a speed of 800-1000 rpm for 10-12 minutes, filtering and washing the mixed solution after stirring to obtain a filter cake, drying the filter cake at 60-70° C. for 22-24 hours, calcining the dried filter cake at 500-550° C. for 1-1.5 hours, and cooling the mixture naturally to obtain the hollow boron nitride microspheres;
[0012] The mass ratio of hexagonal boron nitride to water is 1:(80-90);
[0013] The mass ratio of hexagonal boron nitride to 2-methyl-1,3-butadiene is 1:(55-60);
[0014] The mass ratio of hexagonal boron nitride to polyvinyl pyrrolidone is 1:(3-4);
[0015] The ultrasonic treatment frequency is 10-12kHz;
[0016] The particle size of the boron nitride hollow microspheres ranges from 15 to 20 μm.
[0017] The method for modifying the hollow boron nitride microspheres is as follows: after mixing the hollow boron nitride microspheres and white carbon black, triisostearyl titanate isopropyl is added at a speed of 500-550 rpm and 65-70° C., and stirring is continued for 25-30 minutes at the speed to obtain a boron nitride composite filler;
[0018] The mass ratio of boron nitride hollow microspheres, white carbon black, and isopropyl triisostearyl titanate is 1:(2-2.5):(2-2.5).
[0019] The preparation of the modified porous ceramic particles includes activation and modification;
[0020] The activation method comprises dissolving sodium stannate in water, then adding polyoxyethylene ether and porous ceramic particles, stirring and mixing evenly, adding sodium thiosulfate, continuing to stir for 8-10 minutes, filtering, washing and drying to obtain activated porous ceramic particles;
[0021] The porous ceramic particles are aluminum silicate particles containing zirconium oxide, and the mass ratio of zirconium oxide in the porous ceramic particles is 15-18%;
[0022] The porous ceramic particles have a particle size of 3-5 mm, a pore size of 10-20 μm, and a porosity of 45-55%;
[0023] The mass ratio of porous ceramic particles to water is 15:(100-110);
[0024] The mass ratio of porous ceramic particles to sodium stannate is 15:(1.5-1.8);
[0025] The mass ratio of porous ceramic particles to polyoxyethylene ether is 15:(0.2-0.25);
[0026] The mass ratio of the porous ceramic particles to the sodium thiosulfate is 15:(4-4.5).
[0027] The modification method is to heat the activated porous ceramic particles to 60-65° C., add ethyl orthosilicate and oleic acid under stirring conditions at a speed of 800-900 rpm, and then continue stirring for 10-12 minutes to obtain modified porous ceramic particles;
[0028] The mass ratio of activated porous ceramic particles, tetraethyl orthosilicate and oleic acid is 10:(0.25-0.3):(0.2-0.25).
[0029] The rubber refining method comprises the following steps: plasticizing chloroprene rubber and natural rubber for 60-70 seconds at a temperature of 90-95°C; then adding boron nitride composite filler, modified porous ceramic particles, carbon black, white carbon black and silane coupling agent for primary mixing at a mixing temperature of 130-135°C and a mixing time of 120-130s; then adding a tackifier for secondary mixing at a mixing temperature of 130-135°C and a mixing time of 30-40s; then adding an accelerator and an antioxidant for third mixing at a mixing temperature of 140-145°C and a mixing time of 160-170s; and finally adding sulfur for final mixing at a final mixing time of 90-100s. After the final mixing, the tire tread rubber is obtained.
[0030] In the rubber refining step, the tread rubber includes the following raw material components in parts by weight: 35-40 parts of chloroprene rubber, 60-65 parts of natural rubber, 6-8 parts of boron nitride composite filler, 3-5 parts of modified porous ceramic particles, 15-20 parts of carbon black, 20-30 parts of white carbon black, 6-8 parts of silane coupling agent, 2-3 parts of tackifier, 2-3 parts of sulfur, 2-4 parts of antioxidant, and 1-2 parts of accelerator;
[0031] The carbon black is one of carbon black N330 and carbon black N220;
[0032] The silane coupling agent is one of vinyl triethoxy silane and vinyl trimethoxy silane;
[0033] The tackifier is one of polyisobutylene and terpene resin;
[0034] The antioxidant is one of 4020 and antioxidant RD;
[0035] The accelerator is one of CZ and accelerator TMTD.
[0036] Compared with the prior art, the present invention has the following beneficial effects:
[0037] (1) The present invention utilizes the hollow microsphere structure of the boron nitride composite filler and the porous channel structure of the modified porous ceramic particles to cooperate with each other, which can continuously consume the energy of the sound wave, causing the sound to attenuate, and can also block the propagation path of the sound wave, further enhancing the effect of noise reduction and sound insulation. The tire made of the low-noise tire tread rubber prepared by the method of the present invention is tested for road tire noise according to the far-field trailer method. The noise value is 53.1-54.4dB at a speed of 40km / h, 58.9-59.6dB at a speed of 60km / h, and 63.2-64.0dB at a speed of 80km / h.
[0038] (2) The low-noise tire tread rubber prepared by the present invention can not only reduce noise and sound, but also improve the tensile strength and hardness of the tread rubber. The tire made of the tread rubber has high driving stability and safety. The 300% tensile stress of the low-noise tire tread rubber prepared by the present invention is 15.4-15.8MPa, the tensile strength is 23.2-23.9MPa, the elongation at break is 462-475%, and the hardness is 63-66HA. DETAILED DESCRIPTION
[0039] In order to have a clearer understanding of the technical features, purposes and effects of the present invention, the specific implementation methods of the present invention are now described.
[0040] Example 1
[0041] A method for preparing a low-noise tire tread rubber comprises the following steps: preparing a boron nitride composite filler, preparing modified porous ceramic particles, and refining the rubber;
[0042] (1) Preparation of boron nitride composite fillers
[0043] The following steps are involved:
[0044] a. Preparation of Boron Nitride Hollow Microspheres
[0045] Water, 2-methyl-1,3-butadiene, hexagonal boron nitride and polyvinyl pyrrolidone were prepared into a mixed solution, the temperature of the mixed solution was controlled to be 10°C, and after being stirred and dispersed evenly, ultrasonic treatment was performed at a frequency of 10kHz for 3 minutes, and then stirring was continued at a speed of 800rpm for 12 minutes, and a filter cake was obtained by filtering and washing, and then the filter cake was dried at 60°C for 24 hours, and then the dried filter cake was calcined at 500°C for 1.5 hours, and naturally cooled to obtain boron nitride hollow microspheres;
[0046] The mass ratio of hexagonal boron nitride to water is 1:80;
[0047] The mass ratio of hexagonal boron nitride to 2-methyl-1,3-butadiene is 1:55;
[0048] The mass ratio of hexagonal boron nitride to polyvinyl pyrrolidone is 1:3;
[0049] The particle size of the boron nitride hollow microspheres ranges from 15 to 20 μm.
[0050] b. Modification of Boron Nitride Hollow Microspheres
[0051] Boron nitride hollow microspheres and white carbon black were placed in a magnetic stirrer, triisostearyl titanate isopropyl was added at a speed of 500 rpm and 65° C., and stirring was continued for 30 minutes at the speed to obtain a boron nitride composite filler;
[0052] The mass ratio of the boron nitride hollow microspheres, white carbon black and isopropyl triisostearyl titanate is 1:2:2.
[0053] (2) Preparation of modified porous ceramic particles
[0054] The following steps are involved:
[0055] a. Activation
[0056] Dissolve sodium stannate in water, then add polyoxyethylene ether and porous ceramic particles, stir and mix evenly, then add sodium thiosulfate, continue stirring for 8 minutes, filter, wash, and dry at 50°C to obtain activated porous ceramic particles;
[0057] The porous ceramic particles are aluminum silicate particles containing zirconium oxide, and the mass ratio of zirconium oxide in the porous ceramic particles is 15%;
[0058] The porous ceramic particles have a particle size of 3-5 mm, a pore size of 10-20 μm, and a porosity of 45%;
[0059] The mass ratio of the porous ceramic particles to water is 15:100;
[0060] The mass ratio of the porous ceramic particles to sodium stannate is 15:1.5;
[0061] The mass ratio of the porous ceramic particles to the polyoxyethylene ether is 15:0.2;
[0062] The mass ratio of the porous ceramic particles to sodium thiosulfate is 15:4.
[0063] b. Modification
[0064] Add activated porous ceramic particles into a surface treatment barrel, control the particle temperature to 60°C, add ethyl orthosilicate and oleic acid under stirring at 800 rpm, and continue stirring for 10 minutes to obtain modified porous ceramic particles;
[0065] The mass ratio of the activated porous ceramic particles, tetraethyl orthosilicate and oleic acid is 10:0.25:0.2.
[0066] (3) Rubber refining
[0067] Chloroprene rubber and natural rubber are placed in an internal mixer and plasticized for 60 seconds at a temperature of 90°C; then boron nitride composite filler, modified porous ceramic particles, carbon black N330, white carbon black, and vinyl triethoxysilane are added for a first mixing, the mixing temperature is 130°C, and the mixing time is 120 seconds; then polyisobutylene is added for a second mixing, the mixing temperature is 130°C, and the mixing time is 30 seconds; then accelerator CZ and antioxidant 4020 are added for a third mixing, the mixing temperature is 140°C, and the mixing time is 170 seconds; finally, sulfur is added for final mixing, the final mixing time is 90 seconds, and the tire tread rubber is obtained after the final mixing is completed.
[0068] The tread rubber includes the following raw material components in parts by weight: 35 parts of chloroprene rubber, 65 parts of natural rubber, 6 parts of boron nitride composite filler, 5 parts of modified porous ceramic particles, 15 parts of carbon black N330, 30 parts of white carbon black, 6 parts of vinyl triethoxy silane, 2 parts of polyisobutylene, 2 parts of sulfur, 2 parts of antioxidant 4020, and 1 part of accelerator CZ.
[0069] Example 2
[0070] A method for preparing a low-noise tire tread rubber comprises the following steps: preparing a boron nitride composite filler, preparing modified porous ceramic particles, and refining the rubber;
[0071] (1) Preparation of boron nitride composite fillers
[0072] The following steps are involved:
[0073] a. Preparation of Boron Nitride Hollow Microspheres
[0074] Water, 2-methyl-1,3-butadiene, hexagonal boron nitride and polyvinyl pyrrolidone were prepared into a mixed solution, the temperature of the mixed solution was controlled to be 11°C, and after being stirred and dispersed evenly, ultrasonic treatment was performed at a frequency of 11kHz for 2.5min, and then stirring was continued at a speed of 900rpm for 11min, and a filter cake was obtained by filtering and washing, and then the filter cake was dried at 65°C for 23h, and then the dried filter cake was calcined at 520°C for 1.3h, and naturally cooled to obtain boron nitride hollow microspheres;
[0075] The mass ratio of hexagonal boron nitride to water is 1:85;
[0076] The mass ratio of hexagonal boron nitride to 2-methyl-1,3-butadiene is 1:58;
[0077] The mass ratio of hexagonal boron nitride to polyvinyl pyrrolidone is 1:3.5;
[0078] The particle size of the boron nitride hollow microspheres ranges from 15 to 20 μm.
[0079] b. Modification of Boron Nitride Hollow Microspheres
[0080] Boron nitride hollow microspheres and white carbon black were placed in a magnetic stirrer, triisostearyl titanate isopropyl was added at a speed of 520 rpm and 67° C. The stirring was continued for 28 minutes at the speed to obtain a boron nitride composite filler;
[0081] The mass ratio of the boron nitride hollow microspheres, white carbon black and isopropyl triisostearyl titanate is 1:2.2:2.2.
[0082] (2) Preparation of modified porous ceramic particles
[0083] The following steps are involved:
[0084] a. Activation
[0085] Dissolve sodium stannate in water, then add polyoxyethylene ether and porous ceramic particles, stir and mix well, then add sodium thiosulfate, continue stirring for 9 minutes, filter, wash, and dry at 52°C to obtain activated porous ceramic particles;
[0086] The porous ceramic particles are aluminum silicate particles containing zirconium oxide, and the mass ratio of zirconium oxide in the porous ceramic particles is 16%;
[0087] The porous ceramic particles have a particle size of 3-5 mm, a pore size of 10-20 μm, and a porosity of 50%;
[0088] The mass ratio of the porous ceramic particles to water is 15:105;
[0089] The mass ratio of the porous ceramic particles to sodium stannate is 15:1.6;
[0090] The mass ratio of the porous ceramic particles to the polyoxyethylene ether is 15:0.22;
[0091] The mass ratio of the porous ceramic particles to sodium thiosulfate is 15:4.3.
[0092] b. Modification
[0093] Add the activated porous ceramic particles into the surface treatment barrel, control the particle temperature to 62°C, add ethyl orthosilicate and oleic acid under stirring at 850 rpm, and continue stirring for 11 minutes to obtain modified porous ceramic particles;
[0094] The mass ratio of the activated porous ceramic particles, tetraethyl orthosilicate and oleic acid is 10:0.28:0.22.
[0095] (3) Rubber refining
[0096] Chloroprene rubber and natural rubber are placed in an internal mixer and plasticized for 65 seconds at a temperature of 92°C; then boron nitride composite filler, modified porous ceramic particles, carbon black N330, white carbon black, and vinyl triethoxysilane are added for a first mixing, the mixing temperature is 132°C, and the mixing time is 125 seconds; then terpene resin is added for a second mixing, the mixing temperature is 132°C, and the mixing time is 35 seconds; then accelerator CZ and antioxidant 4020 are added for a third mixing, the mixing temperature is 142°C, and the mixing time is 165 seconds; finally, sulfur is added for final mixing, the final mixing time is 95 seconds, and the tire tread rubber is obtained after the final mixing is completed.
[0097] The tread rubber includes the following raw material components in parts by weight: 40 parts of chloroprene rubber, 60 parts of natural rubber, 7 parts of boron nitride composite filler, 4 parts of modified porous ceramic particles, 18 parts of carbon black N330, 25 parts of white carbon black, 7 parts of vinyl triethoxy silane, 2.5 parts of terpene resin, 3 parts of sulfur, 3 parts of antioxidant 4020, and 1.5 parts of accelerator CZ.
[0098] Example 3
[0099] A method for preparing a low-noise tire tread rubber comprises the following steps: preparing a boron nitride composite filler, preparing modified porous ceramic particles, and refining the rubber;
[0100] (1) Preparation of boron nitride composite fillers
[0101] The following steps are involved:
[0102] a. Preparation of Boron Nitride Hollow Microspheres
[0103] Water, 2-methyl-1,3-butadiene, hexagonal boron nitride and polyvinyl pyrrolidone were prepared into a mixed solution, the temperature of the mixed solution was controlled to be 12°C, and after being stirred and dispersed evenly, ultrasonic treatment was performed at a frequency of 12kHz for 2 minutes, and then stirring was continued at a speed of 1000 rpm for 10 minutes, and a filter cake was obtained by filtering and washing, and then the filter cake was dried at 70°C for 22 hours, and then the dried filter cake was calcined at 550°C for 1 hour, and naturally cooled to obtain boron nitride hollow microspheres;
[0104] The mass ratio of hexagonal boron nitride to water is 1:90;
[0105] The mass ratio of hexagonal boron nitride to 2-methyl-1,3-butadiene is 1:60;
[0106] The mass ratio of hexagonal boron nitride to polyvinyl pyrrolidone is 1:4;
[0107] The particle size of the boron nitride hollow microspheres ranges from 15 to 20 μm.
[0108] b. Modification of Boron Nitride Hollow Microspheres
[0109] Boron nitride hollow microspheres and white carbon black were placed in a magnetic stirrer, triisostearyl titanate isopropyl was added at a speed of 550 rpm and 70° C. The stirring was continued for 25 minutes at the speed to obtain a boron nitride composite filler;
[0110] The mass ratio of the boron nitride hollow microspheres, white carbon black and isopropyl triisostearyl titanate is 1:2.5:2.5.
[0111] (2) Preparation of modified porous ceramic particles
[0112] The following steps are involved:
[0113] a. Activation
[0114] Dissolve sodium stannate in water, then add polyoxyethylene ether and porous ceramic particles, stir and mix evenly, then add sodium thiosulfate, continue stirring for 10 minutes, filter, wash, and dry at 55°C to obtain activated porous ceramic particles;
[0115] The porous ceramic particles are aluminum silicate particles containing zirconium oxide, and the mass ratio of zirconium oxide in the porous ceramic particles is 18%;
[0116] The porous ceramic particles have a particle size of 3-5 mm, a pore size of 10-20 μm, and a porosity of 55%;
[0117] The mass ratio of the porous ceramic particles to water is 15:110;
[0118] The mass ratio of the porous ceramic particles to sodium stannate is 15:1.8;
[0119] The mass ratio of the porous ceramic particles to the polyoxyethylene ether is 15:0.25;
[0120] The mass ratio of the porous ceramic particles to sodium thiosulfate is 15:4.5.
[0121] b. Modification
[0122] Add activated porous ceramic particles into a surface treatment barrel, control the particle temperature to 65°C, add ethyl orthosilicate and oleic acid under stirring at 900 rpm, and continue stirring for 12 minutes to obtain modified porous ceramic particles;
[0123] The mass ratio of the activated porous ceramic particles, tetraethyl orthosilicate and oleic acid is 10:0.3:0.25.
[0124] (3) Rubber refining
[0125] Chloroprene rubber and natural rubber are placed in an internal mixer and plasticized for 70 seconds at a temperature of 95°C; then boron nitride composite filler, modified porous ceramic particles, carbon black N220, white carbon black, and vinyl trimethoxysilane are added for a first mixing, the mixing temperature is 135°C, and the mixing time is 130 seconds; then terpene resin is added for a second mixing, the mixing temperature is 135°C, and the mixing time is 40 seconds; then accelerator TMTD and antioxidant RD are added for a third mixing, the mixing temperature is 145°C, and the mixing time is 160 seconds; finally, sulfur is added for final mixing, the final mixing time is 100 seconds, and the tire tread rubber is obtained after the final mixing is completed.
[0126] The tread rubber includes the following raw material components in parts by weight: 40 parts of chloroprene rubber, 60 parts of natural rubber, 8 parts of boron nitride composite filler, 3 parts of modified porous ceramic particles, 20 parts of carbon black N220, 20 parts of white carbon black, 8 parts of vinyl trimethoxy silane, 3 parts of terpene resin, 3 parts of sulfur, 4 parts of antioxidant RD, and 2 parts of accelerator TMTD.
[0127] Comparative Example 1
[0128] Comparative Example 1 adopts the method for preparing the low-noise tire tread rubber described in Example 2, except that the step of preparing the boron nitride composite filler is omitted, and the addition of the boron nitride composite filler is omitted in the step of preparing the tread rubber.
[0129] Comparative Example 2
[0130] Comparative Example 2 adopts the method for preparing the low-noise tire tread rubber described in Example 2, except that, in the step of preparing the hollow boron nitride microspheres, styrene is used to replace 2-methyl-1,3-butadiene, and the addition of polyvinyl pyrrolidone is omitted.
[0131] Comparative Example 3
[0132] Comparative Example 3 adopts the preparation method of the low-noise tire tread rubber described in Example 2, except that the preparation step of the modified porous ceramic particles is omitted, and the modified porous ceramic particles in the preparation step of the tread rubber are replaced with porous ceramic particles.
[0133] Test Example 1
[0134] First, the tread rubbers prepared in Examples 1-3 and Comparative Examples 1-3 were made into tires using the same existing processing technology. The tires were tested for road tire noise using the remote-field trailer method, that is, the noise between the tires installed on the trailer and the road was tested under inertia conditions. The noise values were tested at vehicle speeds of 40 km / h, 60 km / h, and 80 km / h, respectively. The test results are as follows:
[0135] Table 1 Noise values of tires made of tread rubbers of embodiments and comparative examples
[0136]
[0137] It can be seen from Table 1 that the noise values of the tires made of the tread rubbers of Comparative Examples 1 and 3 at vehicle speeds of 40 km / h, 60 km / h and 80 km / h are significantly higher than those of Example 2, indicating that the noise of the tires made of the tread rubber can be effectively reduced by adding boron nitride composite fillers and modified porous ceramic particles.
[0138] In the method for preparing a boron nitride composite filler of the present invention, hexagonal boron nitride is subjected to thin film climbing in a mixture of 2-methyl-1,3-butadiene and water by an interface capture method, and after ultrasonic treatment, the hexagonal boron nitride stably forms microspheres wrapped with water, and the drying condition of 60-70°C can evaporate the water in the microspheres without causing deformation or rupture of the sphere structure; the hollow boron nitride microspheres are mixed with white carbon black and then modified with triisostearyl titanate isopropyl to obtain a boron nitride composite filler, and triisostearyl titanate isopropyl can make the boron nitride composite filler easily dispersed in a rubber matrix, and the hollow microsphere structure in the boron nitride composite filler can hinder and reflect sound during propagation, thereby reducing the propagation and penetration of sound.
[0139] It can be seen from Table 1 that the noise value of the tire prepared by the tread rubber of Comparative Example 2 is higher than that of Example 2. In the step of preparing hollow boron nitride microspheres in Comparative Example 2, styrene is used to replace 2-methyl-1,3-butadiene, and the addition of polyvinyl pyrrolidone is omitted. The particle size of the prepared hollow boron nitride microspheres is relatively large, and the hollow sphere structure of the microspheres is easily deformed or even broken during the preparation process, which affects the noise reduction effect of the prepared tread rubber.
[0140] In the method for preparing modified porous ceramic particles of the present invention, the porous ceramic particles are activated by sodium stannate, and the polyoxyethylene ether added during the activation process can significantly improve the activity of the particles; after the activated porous ceramic particles are modified by ethyl orthosilicate and oleic acid, the compatibility of the porous ceramic particles with the rubber matrix can be improved, so that the modified porous ceramic particles are evenly dispersed in the rubber. The modified porous ceramic particles have many continuous and tiny holes. When sound waves are transmitted into the porous body, the air in the pores will vibrate and rub inside the material. The sound waves are repeatedly propagated inside the modified porous ceramic particles, and the energy is continuously converted and consumed, thereby achieving the effect of noise reduction.
[0141] In the present invention, the porous channels of the modified porous ceramic particles cooperate with the hollow structure of the microspheres of the boron nitride composite filler, which can not only continuously consume the energy of the sound waves, causing the sound to attenuate, but also block the propagation path of the sound waves, further enhancing the effect of noise reduction and sound insulation.
[0142] The porous ceramic particles and the boron nitride composite filler prepared in the present invention are very strong, can withstand the pressure during the tread rubber preparation process and the tire running, and can maintain the durability of noise reduction.
[0143] Test Example 2
[0144] The 300% modulus stress, tensile strength, elongation at break, and hardness of the tread rubbers prepared in Examples 1-3 and Comparative Examples 1-3 were tested, and the test results are as follows:
[0145] Table 2 Parameters related to tread strength and hardness of the examples and comparative examples
[0146]
[0147] It can be seen from Table 2 that the 300% modulus of tensile stress, tensile strength, elongation at break and hardness of the tread rubbers of Comparative Examples 1 and 3 are significantly lower than those of Example 2, indicating that the boron nitride composite filler and modified porous ceramic particles added to the tread rubber can significantly improve the tensile strength and hardness of the tread rubber.
[0148] In the method for preparing the boron nitride composite filler of the present invention, hexagonal boron nitride is peeled off at the oil-water interface, and the microspheres formed after ultrasound are very strong after drying and calcination, and in the boron nitride hollow microsphere modification step, white carbon black is adsorbed around the boron nitride hollow microspheres, which can further improve the strength of the boron nitride composite filler, so that the boron nitride composite filler will not be broken due to extrusion during the preparation process of the tread rubber and the running process of the prepared tire, and the tensile strength and hardness of the tread rubber can be improved.
[0149] The present invention uses porous ceramic particles of aluminum silicate rich in zirconium oxide, which have high hardness, are structurally stable during the tread rubber preparation process and during tire driving, are not easy to break, and can also improve the tensile strength and hardness of the tread rubber to a certain extent. The unmodified porous ceramic particles used in Comparative Example 3 have relatively poor compatibility in the rubber matrix, and the ceramic particles have too smooth a surface and low surface energy, which makes it difficult to form a good combination with the rubber matrix, resulting in uneven dispersion, affecting the tensile strength and hardness of the tread rubber.
[0150] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing a low-noise tire tread rubber, characterized in that: The method for preparing the tread rubber comprises the following steps: preparing a boron nitride composite filler, preparing modified porous ceramic particles, and refining the rubber; The preparation of the boron nitride composite filler includes preparing boron nitride hollow microspheres and modifying the boron nitride hollow microspheres; The method for preparing hollow boron nitride microspheres comprises: preparing a mixed solution of water, 2-methyl-1,3-butadiene, hexagonal boron nitride and polyvinyl pyrrolidone, controlling the temperature of the mixed solution to be 10-12° C., stirring and dispersing the mixed solution uniformly, ultrasonically treating the mixed solution for 2-3 minutes, stirring the mixed solution at a speed of 800-1000 rpm for 10-12 minutes, filtering and washing the mixed solution to obtain a filter cake, drying the filter cake at 60-70° C. for 22-24 hours, calcining the dried filter cake at 500-550° C. for 1-1.5 hours, and cooling the mixture naturally to obtain the hollow boron nitride microspheres; The method for modifying the hollow boron nitride microspheres is as follows: after mixing the hollow boron nitride microspheres and white carbon black, triisostearyl titanate isopropyl is added at a speed of 500-550 rpm and 65-70° C., and stirring is continued at the speed for 25-30 minutes to obtain a boron nitride composite filler; The preparation of the modified porous ceramic particles includes activation and modification; The activation method comprises dissolving sodium stannate in water, then adding polyoxyethylene ether and porous ceramic particles, stirring and mixing evenly, adding sodium thiosulfate, continuing to stir for 8-10 minutes, filtering, washing and drying to obtain activated porous ceramic particles; The modification method is to heat the activated porous ceramic particles to 60-65° C., add ethyl orthosilicate and oleic acid under stirring conditions at a speed of 800-900 rpm, and then continue stirring for 10-12 minutes to obtain modified porous ceramic particles; The tread rubber comprises the following raw material components in parts by weight: 35-40 parts of chloroprene rubber, 60-65 parts of natural rubber, 6-8 parts of boron nitride composite filler, 3-5 parts of modified porous ceramic particles, 15-20 parts of carbon black, 20-30 parts of white carbon black, 6-8 parts of silane coupling agent, 2-3 parts of tackifier, 2-3 parts of sulfur, 2-4 parts of antioxidant, and 1-2 parts of accelerator; The carbon black is one of carbon black N330 and carbon black N220; The silane coupling agent is one of vinyl triethoxy silane and vinyl trimethoxy silane; The tackifier is one of polyisobutylene and terpene resin; The antioxidant is one of 4020 and antioxidant RD; The accelerator is one of CZ and accelerator TMTD.
2. The method for preparing a low-noise tire tread rubber according to claim 1, characterized in that: In the step of preparing hollow boron nitride microspheres, The mass ratio of hexagonal boron nitride to water is 1:(80-90); The mass ratio of hexagonal boron nitride to 2-methyl-1,3-butadiene is 1:(55-60); The mass ratio of hexagonal boron nitride to polyvinyl pyrrolidone is 1:(3-4); The sonication frequency was 10-12 kHz.
3. The method for preparing a low-noise tire tread rubber according to claim 1, characterized in that: In the step of preparing the hollow boron nitride microspheres, the particle size of the hollow boron nitride microspheres is in the range of 15-20 μm.
4. The method for preparing a low-noise tire tread rubber according to claim 1, characterized in that: In the boron nitride hollow microsphere modification step, the mass ratio of the boron nitride hollow microsphere, white carbon black, and isopropyl triisostearyl titanate is 1:(2-2.5):(2-2.5).
5. The method for preparing a low-noise tire tread rubber according to claim 1, characterized in that: In the activation step, The porous ceramic particles are aluminum silicate particles containing zirconium oxide, and the mass ratio of zirconium oxide in the porous ceramic particles is 15-18%; The porous ceramic particles have a particle size of 3-5 mm, a pore size of 10-20 μm, and a porosity of 45-55%.
6. The method for preparing a low-noise tire tread rubber according to claim 1, characterized in that: In the activation step, The mass ratio of porous ceramic particles to water is 15:(100-110); The mass ratio of porous ceramic particles to sodium stannate is 15:(1.5-1.8); The mass ratio of porous ceramic particles to polyoxyethylene ether is 15:(0.2-0.25); The mass ratio of the porous ceramic particles to the sodium thiosulfate is 15:(4-4.5).
7. The method for preparing a low-noise tire tread rubber according to claim 1, characterized in that: In the modification step, the mass ratio of activated porous ceramic particles, tetraethyl orthosilicate and oleic acid is 10: (0.25-0.3): (0.2-0.25).
8. The method for preparing a low-noise tire tread rubber according to claim 1, characterized in that: The rubber refining method comprises the following steps: plasticizing chloroprene rubber and natural rubber for 60-70 seconds at a temperature of 90-95°C; then adding boron nitride composite filler, modified porous ceramic particles, carbon black, white carbon black and silane coupling agent for primary mixing at a mixing temperature of 130-135°C and a mixing time of 120-130s; then adding a tackifier for secondary mixing at a mixing temperature of 130-135°C and a mixing time of 30-40s; then adding an accelerator and an antioxidant for third mixing at a mixing temperature of 140-145°C and a mixing time of 160-170s; and finally adding sulfur for final mixing at a final mixing time of 90-100s. After the final mixing, the tire tread rubber is obtained.
9. The tread rubber prepared by the preparation method according to any one of claims 1 to 8.
Citation Information
Patent Citations
Low-noise pneumatic tire
CN110039964A
Structure for reducing noise of tire cavity
CN112659819A
Lower tread rubber composition for reducing tire noise and pneumatic tire
CN113929960A
Sound-insulating ceramic material
CN109336616A
Tread rubber with noise reduction performance, preparation method of tread rubber and tire
CN116656021A